Sociobehavioural risk factors of dental caries among selected adolescents in Ibadan, Nigeria (2014)
Objective: The objective of this study was to determine the inﬂuence of sociodemographic and behavioural factors on the prevalence of dental caries among the adolescents in Ibadan. Method: Multistage sampling method was used to select participants from six secondary schools. In each school, an arm was selected randomly from each class and 30 students also randomly chosen per arm, with equal distribution of males and females. A structured questionnaire was administered. It consisted two parts, the ﬁrst part assessed information on the sociodemographic characteristics, oral health behaviours and snacking habits of respondents, while the second part consisted of intra-oral examination to determine the caries status and oral hygiene (OH) levels of respondents. Result: The age range of the participants was 10e19 years with a mean of 13.73 2.02 years. The father’s level of education had a statistically signiﬁcant association with dental caries; prevalence of dental caries was high in the 10e14-years age group, in children of parents from high socio-economic (SE) class, those who reported brushing twice daily, those with poor OH and those who ate snacks in between their meals. Conclusion: This study reveals that high SE status, poor OH and daily consumption of biscuits were important factors in caries experience among the school children studied. Copyright ª 2014 The Japanese Society of Pediatric Dentistry. Published by Elsevier Ltd. All rights reserved.